2015
DOI: 10.1016/j.mechmat.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation and numerical modeling of formation of local plastic zones in hardened surface layers due to contact overloading

Abstract: a b s t r a c tThe problem of formation of plastic zones in case-hardened metallic bodies due to contact overloading is studied both experimentally and numerically. Metallic materials exposed to surface hardening demonstrate spatial variation of the material hardness and yield strength with a decreasing profile with depth and belong to the class of so-called plastically graded materials. The presented experimental program employs micro-Vickers hardness tests to map the variation in material hardness and corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Previous experiments and numerical modelling of local contact loading of cylinders with a plastically graded surface layer [15] have shown that plastic deformation initiates with formation of a closed-shape plastic region at some depth without reaching the surface. Maximum plastic strains form at the depths of 1.5 − 2 of half the contact length , which exceed the depth at which the maximum effective stress develops in purely elastic contact conditions (0.785 , according to the Hertz solution).…”
Section: Problem Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous experiments and numerical modelling of local contact loading of cylinders with a plastically graded surface layer [15] have shown that plastic deformation initiates with formation of a closed-shape plastic region at some depth without reaching the surface. Maximum plastic strains form at the depths of 1.5 − 2 of half the contact length , which exceed the depth at which the maximum effective stress develops in purely elastic contact conditions (0.785 , according to the Hertz solution).…”
Section: Problem Formulationmentioning
confidence: 99%
“…We consider a twodimensional problem of a case-hardened half-plane, representing the roll, with a plastically graded surface layer in contact with an elastic circular disc, while the total contact load and the radius of the disc are chosen such that the corresponding loading parameters (mean load pressure p and contact length 2b) are in accordance with the estimates of the illustrative example, described in the previous section ( Table 1). Validation of the model can be found in [15]. The straight boundary eliminates the influence of the contact surface curvature of the plastically graded body on the distribution of stress/strain fields in the near-contact zones.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations